Analysis of Financial Performance of Industrial Sector Companies Through Liquidity, Leverage and Efficiency Ratios - Yudia Setya Andini; Imronudin (Journal of Governance, Taxation and Auditing, 2026)
In a highly competitive industrial landscape, maintaining financial strength has become essential for a firm’s long-term viability. Profitability—captured most directly through Return on Assets (ROA)—reflects how effectively a company converts its assets into earnings. This study examines how three key financial indicators shape ROA: the Current Ratio, representing short-term financial resilience; the Debt to Equity Ratio, reflecting the structure and risk profile of corporate financing; and Total Asset Turnover, indicating how efficiently assets are mobilized to generate revenue. By assessing these ratios in industrial companies listed on the Indonesia Stock Exchange during 2021–2024, the research provides a concise overview of how liquidity, leverage, and asset efficiency collectively influence corporate profitability. Each ratio reflects a different aspect of financial health: CR describes the company’s liquidity position, DER indicates its leverage and risk exposure, while TATO captures the degree to which its assets are effectively used to generate sales. The focus on this period is driven by the economic instability associated with the COVID-19 pandemic and its recovery phase, which may have reshaped corporate financial dynamics. Previous studies examining these ratios simultaneously within the industrial sector remain limited. The results of this study are anticipated to contribute to the broader academic discourse on the factors that influence corporate financial performance, while also providing practical guidance for managers and investors who aim to improve a company’s profitability.